Metabolic Crisis in Neurocritical Care: Definition, Classification, and Bundle of Therapeutic Interventions for the Acute and Hyperacute Stages - Kundu, Mrinmoy; Abdulla, Ebtesam; Janjua, Tariq; Flores-Perdomo, William A.; Salazar, Luis Rafael Moscote (Indian Journal of Neurotrauma, 2025)
Metabolic crisis in neurocritical care is a critical condition with significant implications for patient outcomes. This review provides a comprehensive examination of metabolic crisis, focusing on its definition, classification, and bundle of therapeutic interventions for the acute and hyperacute stages. A metabolic crisis is a severe metabolic disturbance that occurs in patients with acute neurological injuries, leading to an imbalance in energy substrates. This imbalance can exacerbate the initial neurological injury and result in poor patient outcomes. The metabolic crisis poses a significant threat to CNS function, leading to neuronal injury, oxidative stress, and other detrimental effects. Early detection and prompt intervention are crucial to effectively manage metabolic crisis, as delaying treatment can result in severe and irreversible consequences. Implementing a bundle approach is crucial for improving outcomes in the acute and hyperacute stages of metabolic crisis. Pharmacological interventions play a key role, such as using glucose-lowering agents to address hyperglycemia, administering antiepileptic drugs to control seizures, and utilizing sodium bicarbonate to correct metabolic acidosis. Non-pharmacological interventions are also vital, including strict glycemic control, optimization of oxygenation, ventilation, and perfusion, as well as temperature control to minimize secondary brain injury and promote neurological recovery.
Keywords: metabolic crisis; neurocritical care; neurotrauma; acute neurological injuries; bundle approach